The Role of Color in Human Practice - Karimova Dilnoza Erkinovna; Muqimova Zarina Uyg’unqizi (Researchparks Publishing, 2022)
This article discusses the role of stress in human practice. Color is widely used both in art and in the organization of production processes to increase labor productivity and reduce employee fatigue, which contributes to active and complete recreation of people, as well as to provide comfort at home, create a psychological emphasis. is the active substance used